Pengaruh Model Pembelajaran Advance Organizer Terhadap Hasil Belajar Siswa SMA Negeri 3 Sigi pada Materi Larutan Elektrolit dan Non Elektrolit - Maryam, Maryam; Ratman, Ratman; Ningsih, Purnama (Universitas Tadulako, 2018)
This study aimed to determine the influence of advance organizer learning model toward learning achievements of students at SMA Negeri 3 Sigi on the topic electrolyte and non-electrolyte solutions. This study was a quasi-experiment with pretest-posttest control group design using two groups of students, i.e. 34 Class X B as an experimental group , and 34 Class X A as a control group. Data of learning achievements of students was analyzed using t-test two parties statistical analysis. Results showed that the average values of experiment class (X1) was 77.15 with a standard deviation of 11.59, while the average values of control class (X2) was 68.44 with a standard deviation of 10.73. This testing hypotheses with statistical t-test two parties obtained -ttable â‰¤ tcount Â³ + ttable (tcount = 10.89 and ttable = 2.00) with a significant level a = 0.05, and degrees of freedom 66. Therefore, H0 was rejected, and HI was accepted. This study concluded that advance organizer learning model influenced learning achievements of students at SMA Negeri 3 Sigi on the topic electrolytes and non-electrolyte solutions.